Domestic politics and the formation of international environmental agreements - Simon Dietz; Carmen Marchiori; Alessandro Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2012)
The theory of international environmental agreements overwhelmingly assumes that governments engage as unitary agents. Each government makes choices based on benefits and costs that are simple national aggregates, and similarly on a single set of national-level motivations, together drawing a strong analogy with the behaviour of an individual or firm in other strategic contexts. In reality, however, various domestic special interests shape environmental policy, including how national governments cooperate on cross-border issues. Therefore in this paper we introduce to a classic model of international environmental cooperation the phenomenon of domestic political competition, whereby lobby groups seek to influence policy by offering to fund political campaigning. We use the model to establish some general conditions for the effects of lobbying on the stringency of policy and the size of coalitions cooperating to provide an environmental good. Using specific functional forms, we obtain a range of further results, including circumstances in which the omission of lobbying results in environmental protection being underestimated.
Keywords: C7; H41; K33; Q2; Q54; 330; Game Theory; International Environmental Agreements; Lobbying; Special-Interest Groups; Strategic Cooperation